2012
DOI: 10.2169/internalmedicine.51.6417
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Bilirubin Level is Related to Good Collateral Development in Patients with Chronic Total Coronary Occlusion

Abstract: Objective Bilirubin is a bile pigment with potent anti-oxidant properties; in previous studies it has been reported to be negatively associated with coronary artery disease (CAD). Although elevated serum bilirubin concentrations may protect against endothelial dysfunction, it is not clear whether higher serum bilirubin levels (SBLs) in physiological ranges may work in favor of good collateral development in patients with chronic total coronary occlusion (CTO). Methods The study population consisted of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
(40 reference statements)
1
20
0
1
Order By: Relevance
“…Erdogan et al . [20] evaluated undergoing coronary angiography for CAD and found that greater bilirubin levels were related to favorable coronary collateral flow in patients with chronic total occlusion. Okuhara et al .…”
Section: Discussionmentioning
confidence: 99%
“…Erdogan et al . [20] evaluated undergoing coronary angiography for CAD and found that greater bilirubin levels were related to favorable coronary collateral flow in patients with chronic total occlusion. Okuhara et al .…”
Section: Discussionmentioning
confidence: 99%
“…Erdogan et al (41) first investigated the possible effects of serum bilirubin on coronary collateral development in patients with CAD who experienced total coronary occlusion. This study indicated that serum total bilirubin concentrations were positively related to collateral development.…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 99%
“…This study indicated that serum total bilirubin concentrations were positively related to collateral development. NO plays a crucial role in the development of collateral vessels, and therefore bilirubin may be an important mediator increasing NO bioavailability, augmenting collateral development (41) and reducing amputation rates in type II diabetic patients (23). NO is considered the most important endothelium-derived relaxing substance (54), with endothelial dysfunction often characterized by a loss of NO bioavailability.…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 99%
“…Earlier researches have demonstrated an inverse correlation between serum bilirubin and the risk of coronary artery disease and decreased antioxidant activity of bilirubin in atherosclerotic lesions [1, 2]. Recent studies have confirmed the correlation between serum bilirubin levels and collateral development in patients with chronic total coronary occlusion [3], peripheral arterial disease [4], amputation events in type-2 diabetes mellitus [5], stroke severity and clinical outcomes [6]. Those results suggested that bilirubin may be a part of a cell defense strategy in those macro- and micro- angiopathies.…”
Section: Introductionmentioning
confidence: 99%